Effects of zeolite and bismuth oxide addition on structural, thermal, optical, and electrical behaviour of conducting polymer polypyrrole - Mohd Tarmizi, Emma Ziezie (2015)
Polypyrrole (PPY), Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide powders were successfully synthesized through the chemical oxidation polymerization method containing pyrrole monomer, iron (III) chloride hexahydrate as primary doping agent and Zeolite and Bismuth oxide as secondary doping agents. The Polypyrrole, Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide conjugated systems prepared at different concentration percentages ranging from 0 % to 20 %. The structural, compositional, morphological, thermal, optical, magnetic and electrical properties of the synthesized compound were characterized by X-ray diffraction (XRD) analysis, Energy Dispersion X-Ray Fluorescence (ED-XRF), Fourier Transform Infrared (FTIR), Field Emission Scanning Elelctron Microscope (FESEM), Thermogravimetry Analysis (TGA), Electron Spin Resonance (ESR), Laser Flash measurement, Diffuse Reflectance Spectroscopy (DRS) and Van Der Pauw (VDP) technique. XRD confirmed the amorphous characteristic peak structure of pristine Polypyrrole at two theta ~25o. The impregnation of Zeolite and Bismuth oxide resulted in the presence of sharp peak which implies that both Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide has some degree of crystallinity and more ordered arrangement than those pristine of Polypyrrole conjugated system. The elemental analysis confirmed the presence of primary and secondary doping agents in all Polypyrrole conjugated systems and witnessed the increment of every element as it were increased. This is in agreement with FTIR analysis which revealed the successful incorporation of primary and secondary doping agents in Polypyrrole conjugated systems through its nearly identical and positions of IR absorption bands of Polypyrrole, Zeolite and Bismuth oxide to which is available in literature. The FESEM morphology showed the formation of Polypyrrole, Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide revealing a globular images or cauliflower morphology of Polypyrrole. It also revealed that all the agents of primary and secondary doping have complete miscibility with Pyrrole forming a Polypyrrole, Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide.Thermal stability is mainly studied by TGA. It was observed that the impregnation of Zeolite and Bismuth oxide in the conjugated system have shown a remarkable improvement on thermal stability of Polypyrrole conjugated systems which suggested that the structure formed is well orderly structured and strong. The ability of Polypyrrole, Polypyrrole/Zeolite and Polpyrrole/Bismuth oxide conjugated systems to transit heat was measured using Flash technique. Higher molecular weight and higher crystallinity resulted from Zeolite and Bismuth oxide are believed to increase the conjugation length and providing more through-space pathways for electron to migrate and thus increased the thermal diffusivity. Three peaks of absorbance are observed for Polypyrrole, Polyprrole/Zeolite and Polypyrrole/Bismuth oxide at different photon energy which are believed to be associated with transitions from below band edge to bonding and anti-bonding levels of polarons (band gap), bonding to anti-bonding levels of polarons (intraband), and valence band to conduction band (interband). Estimation of energy gap using Kabelka-Munk treatment revealed that the incorporation of secondary doping agents of Zeolite and Bismuth oxide changed the energy gap to a smaller range value. Presence of polaron in all samples was confirmed by ESR spectroscopy technique. The spin number (Ns) was determined and found to depend on primary and secondary doping agent concentrations level in Polypyrrole conjugated system. ESR linewidth showed temperature dependence and suggests the validity of the Elliot relaxation for Polypyrrole, Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide conjugated system. The electrical conductivity studies were investigated using Van Der Pauw technique at temperature range between 20 K until 300 K. From the results, it was observed that the electrical conductivity increased with increasing of primary and secondary doping agents in Polypyrrole conjugated systems. It was found that the electrical conductivity of pristine Polypyrrole, Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide conjugated systems strongly depends on the applied temperature. There were two regimes of electrical conductivity observed where the first regime is from 20 K to 50 K and the second regime starts from 50 K up to 300 K. Temperature dependence of conductivity of pristine Polypyrrole, Polypyrrole/Zeolite and Polypyrrole/Bismuth oxide conjugated systems samples between temperatures of 50 K until 300 K suggests a transition from semiconducting nature to metallic nature. In the temperature range from 50 K to 300 K range, the charge carrier mechanism was dominated by 3-D variable range hopping mechanism, VRH transport.